2021
DOI: 10.1371/journal.pone.0255576
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific genetic variability and diurnal activity affect environmental DNA detection in Japanese eel

Abstract: Environmental DNA (eDNA) analysis with species-specific primer/probe sets is promising as a tool to quantify fish abundance and distribution. Nevertheless, several factors could reduce the accuracy of this method. Here, we aimed to analyze whether intraspecific variability and diel activity rhythm affect eDNA detection in Japanese eels (Anguilla japonica). For this purpose, we performed tank experiments focusing on two points. First, we assessed the effects of base pair sequences with probe region polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Diurnal changes in fish eDNA concentrations could be caused by simple changes in biomass or activity levels as well as spawning, but previous studies and our observations would rule out these possibilities. In the only previous study about diurnal changes in eDNA concentration, a slight increase in eDNA levels associated with nocturnal activity in nocturnal fish, Japanese eels ( Anguilla japonica ), was reported by aquarium experiments (Takahashi et al, 2021). In contrast, previous studies on nocturnal amphibians found no differences in eDNA concentrations between daytime and nighttime ( Cryptobranchus a. alleganiensis , Takahashi et al, 2018; Ascaphus montanus and Dicamptodon aterrimus , Pilliod et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Diurnal changes in fish eDNA concentrations could be caused by simple changes in biomass or activity levels as well as spawning, but previous studies and our observations would rule out these possibilities. In the only previous study about diurnal changes in eDNA concentration, a slight increase in eDNA levels associated with nocturnal activity in nocturnal fish, Japanese eels ( Anguilla japonica ), was reported by aquarium experiments (Takahashi et al, 2021). In contrast, previous studies on nocturnal amphibians found no differences in eDNA concentrations between daytime and nighttime ( Cryptobranchus a. alleganiensis , Takahashi et al, 2018; Ascaphus montanus and Dicamptodon aterrimus , Pilliod et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, on day2-18:00, eDNA concentrations tended to increase again, surpassing the levels observed during the day (P<0.05). In the only previous study about diurnal changes in eDNA concentration, a slight increase in eDNA levels associated with nocturnal activity in nocturnal fish, Japanese eels (Anguilla japonica), was reported by aquarium experiments 45 . In contrast, previous studies on nocturnal amphibians found no differences in eDNA concentrations between daytime and nighttime (Cryptobranchus a. alleganiensis 16 , Ascaphus montanus and Dicamptodon aterrimus 46 ).…”
Section: Substantial Diurnal Change In Edna Concentration During the ...mentioning
confidence: 94%
“…Molecular identification of eels has been successfully conducted (Arai et al, 2020;Alter et al, 2015;Wibowo et al, 2021). Furthermore, detection of the presence and diversity of eel revealed by environmental DNA analysis (Kasai et al, 2021;Takahashi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%